HUBUNGAN ANTARA DUKUNGAN SOSIAL DAN PENERIMAAN DIRI PADA PASIEN DENGAN PENYAKIT GINJAL KRONIS - Rosnancy Sinaga; Ariyanti Yolanda Bakara (Fakultas Ilmu Keperawatan Universitas Advent Indonesia, 2019)
Patients diagnosed with chronic kidney disease who undergo hemodialysis therapy often feel discouraged, lack of self-acceptance and feeling not useful for the family and the surrounding environment. Furthermore, patients who undergo hemodialysis often feel depression of the disease. The purpose of this study was to explore the relationship between the social support and selfacceptance in patients with chronic kidney disease. This study utilized a descriptive correlational research design to describe the relationship. Before the data collection, the researchers secured an administrative clearance from the hospital. The samples were 30 patients with chronic kidney disease and undergo hemodialysis therapy in the hospital. Two sets of questionnaires were disseminated, and responses were treated analyzed using descriptive statistics to describe the demographic profile, while Spearman Rank test was used to measure the relationship between social support and self-acceptance in patients with chronic kidney disease. Using valid questionnaires, the patients rated their level of social support as good (82.08%). Participants agreed that the level of self-acceptance was good (71.42%). The findings indicate that social support was correlated with self-acceptance in patients with chronic kidney disease (r=0.850, pË‚0.00). The study concludes that there was strong relationship between social support and selfacceptance in the patients with chronic kidney disease who undergo hemodialysis therapy. Keywords: chronic kidney disease, social support, self-acceptance